Teachers Love as a Predictor of Buddhist Students Moral Action in Central Java - Sukodoyo Sukodoyo (Jurnal Cakrawala Pendidikan, 2018)
Abstract: The aim of this study was to investigate the effect of teachers loving kindness on the moral action of junior high school Buddhist students in Central Java. This ex-post facto study involved a total sample of 396 students out of the total population of 732 Budhist students  in  Central  Java.  A  questionnaire  was  used  to  collect  the  data  in  this  study. Regression analysis was used to find out the effect of teachers loving kindness on students moral action. The results show that: (1) there is a positive and significant impact of the teachers loving kindness perception on the moral action junior high school Buddhist students in Central Java; (2) there is a positive correlation between teacher loving kindness perception (X) and students moral action (Y) (r= .317); (3) the contribution of teachers loving kindness on the moral action for junior high school Buddhist students in Central Java was 0.101 or 10.1%; (4) the regression equation is Y = 50,202 + 0,237X.Keywords: teachers loving kindness, moral action, Buddhist students PERAN CINTA KASIH GURU SEBAGAI PREDIKTOR TINDAKAN MORAL SISWA BUDDHIS SMP DI JAWA TENGAHAbstrak: Tujuan penelitian ini adalah memberikan rekomendasi tentang peran cinta kasih guru sebagai prediktor tindakan moral diswa Buddhis SMP. Penelitian ini menggunakan pendekatan ex-post facto. Populasi dalam penelitian ini adalah siswa Buddhis SMP di Jawa Tengah yang berjumlah 732 siswa dan sampel penelitian berjumlah 396 siswa yang diambil dengan teknik simple random sampling yang berasal dari 21 SMP. Teknik pengumpulan data dilakuan  dengan  menggunakan  angket.  Validitas  instrumen  yang  dihitung lewat  korelasi produk moment dinyatakan valid dengan indeks antara 0,300-0,788, sedang reliabilitas yang dihitung lewat teknik alpha Cronbach diperoleh indeks 0,932. Data dianalisis dengan teknik regresi. Hasil penelitian menunjukkan: (1) terdapat pengaruh positif dan signifikan persepsi tentang peran cinta kasih guru sebagai prediktor tindakan moral siswa Buddhis SMP di Jawa Tengah; (2) terdapat korelasi antara cinta kasih guru (X) dengan tindakan moral siswa (Y) sebesar 0,317  yang berada pada kategori  rendah; (3) sumbangan peran  cinta kasih guru terhadap tindakan moral siswa Buddhis SMP di Jawa Tengah sebesar 0,101 atau 10,1%; (4) persamaan garis regresi Y= 50,202 + 0,237X.Kata Kunci: cinta kasih guru, tindakan moral siswa Buddhis